Real-time deep learning-based market demand forecasting and monitoring. (May 2022) - Guo, Yuan; Luo, Yuanwei; He, Jingjun; He, Yun
Highlights: Develop a CNN algorithm consists of two parts of feature extraction and classification in one model which makes it a unique and practical model in the area. Develop a model to find the highest effective features for the market demand prediction Training the CNN hyper parameters using a heuristic model based on PSO. Considering the very complexity of the market demand in the new competitive environment using a novel fuzzy-based PSO Use the fuzzy membership concept with aid of PSO to change its parameters dynamically rather than considering constant values. Abstract The concept of market demand forecasting is a very precious and significant problem in the industry without which the generator companies would not be able to give a suitable offer and may experience big losses. This research introduces a novel deep learning based on convolutional neural networks (CNN) to learn the market behavior in details. The model comprises a weight update mechanism in the backpropagation process of CNN to enhance its performance. Moreover, a fuzzy particle swarm optimization (FPSO) based algorithm is used to enhance the CNN performance and find the most accurate predictions. The proposed FPSO would utilize the fuzzy set theory and membership function to update the weighting coefficients. To validate this proposal, real market demand data are used as the benchmark and the results are discussed in the paper. The simulation results prove the suitable performance of the proposed CNN-FPSO model. Abstract : Image, graphical abstract